Investigating Professional Identity Development Through Arts-Based Duoethnography - Chien, Ting Fang; Yang, Hsiu-Chun (Art/Research International)

(untitled) (University of Alberta, 2024)
This study employs an arts-based duoethnographic approach to contemplate the nuances of and understand the struggles that two researchers confronted in their new professional roles as art educators. The investigation focuses on how conversations, art practices, and reflective/diffractive analysis can help with understanding or processing professional identity development. The data include art practices, field notes, monthly meetings, and emails sent between February and May 2019. The main content of this article presents the two researchers’ exchange of emails and art pieces as part of the preliminary data analysis. Two pivotal elements stand out in the exploration: diffracting relationships and deconstructing perspectives that support growth and development during the process. Additionally, the investigation affirms that positive differences can be produced even though two researchers hold distinct perspectives. The methodology supports professional identity development as an ongoing and deconstructing process of searching for differences and being different.